Petrogenesis of Late Cretaceous mafic enclaves and their host granites in the Nyemo region of southern Tibet: Implications for the tectonic-magmatic evolution of the Central Gangdese Belt. (1st June 2019) - Meng, Yuanku; Xiong, Fahui; Xu, Zhiqin; Ma, Xuxuan
Graphical abstract: Highlights: MMEs and hosting granites in the Nyemo region, southern Tibet, formed at 84–87 Ma. Magma mixing was an important process to form both the hosting granites and MMEs. Late Early Cretaceous adakite-like granites were related to hornblende fractionation and underplating of mafic magmas. Rollback of the Neo-Tethys was responsible for Late Cretaceous magmatic flare-up. Abstract: Late Triassic-Early Eocene Gangdese magmatic belt is over 2000 km long forming a significant component of the Lhasa Terrane, and is regarded as the ideal place to study the tectonic-magmatic evolution of the Neo-Tethys Ocean and the collision of the Indian and Asian continental plates. Recent studies elucidate the major Late Cretaceous magmatic events in southern Tibet, but the evolution of the region is still equivocal. In this paper, we report new results from systematic field work as well as new geochronological, petrological, geochemical, and zircon Lu-Hf isotope analyses of granite and contemporaneous mafic microgranular enclaves (MMEs) from the Nyemo region in southern Tibet. Both the host granite and MMEs are dated at ca. 87–84 Ma, suggesting that they are related to a coeval magmatic event. Zircon Hf isotopes (εHf (t) = +11.0 – +14.6) and Mg # numbers (50–52) indicate that the host granite is derived from partial melting of juvenile crust with the contribution of material from the mantle, whereas the MMEs are derived from partial melting of depleted mantle (refractory peridotite melts) as deduced from their zircon Hf isotopes (εHf (t) = +6.12 – +13.79). Geochemically, both the granite and MMEs are characterized by enriched light rare earth elements (LREE) and large-ion lithophile elements (LILE), but depleted high field-strength elements (HFSE), indicative of arc-related geochemical compositions. The host granite also has high Sr/Y (111–140), which are interpreted as proxies for magmas with high water contents, and their elevated (La/Yb)N ratios of 22–33 are proxies for a thickened continental crust. We propose that the Late Cretaceous (ca. 100–80 Ma) magmatism dated some 30 million years before the collision of the Indian and Eurasian plates is possibly related to the interaction between upwelling asthenospheric mantle and metasomatized lithospheric mantle during subduction and possible rollback of the Neo-Tethys Oceanic plate. The subducted slab presumably led to mantle magma underplating and potentially caused crustal thickening in southern Tibet. Hence, the rollback of the Neo-Tethys Oceanic plate represents a key feature in the tectonic evolution of southern Tibet during the early Late Cretaceous.